ALDOSTERONE CONTRIBUTES TO SYSTOLIC BLOOD PRESSURE ELEVATION DURING REST TIME IN MALE MICE INDUCIBLY OVEREXPRESSING HUMAN ENDOTHELIN-1 IN ENDOTHELIUM. (April 2021) - Berillo, Olga; Mahjoub, Nada; Coelho, Suellen C.; Offermanns, Stefan; Paradis, Pierre; Schiffrin, Ernesto L.
Abstract : Objective: The mechanisms of blood pressure (BP) regulation by endothelin (ET)-1 produced by endothelial cells (ECs) are complex and remain unclear. Transgenic mice with tamoxifen-inducible EC-restricted human ET-1 overexpression (ieET-1) exhibited BP elevation 3 months after induction. ET-1 has been shown to stimulate the release of aldosterone from adrenal cortex (AC). Whether aldosterone plays a role in EC ET-1 overexpression-induced BP elevation and vascular injury is still unknown. Design and method: Nine to 12-week-old male ieET-1 mice and control ieCre mice expressing a tamoxifen-inducible Cre recombinase under the control of EC-specific Tie2 promoter were treated with tamoxifen (1 mg/kg/day, SC) for 5 days and studied 3 months later. A set of mice was treated with eplerenone (100 mg/kg/day, PO), a mineralocorticoid receptor antagonist, or the ETA receptor blocker atrasentan (100 mg/kg/day) during the last 2 weeks of the study. BP was measured by telemetry and mesenteric artery function and remodeling by pressurized myography. Plasma aldosterone levels were measured by ELISA. The expression of genes involved in aldosterone biosynthesis was determined by reverse transcription-quantitative PCR in AC. CYP11B2 expression was determined in AC by immunofluorescence. Results: Plasma aldosterone levels were increased in ieET-1 vs. ieCre mice (1.21 ± 0.14 vs. 0.70 ± 0.09 ng/mL, P < 0.05), which was reversed by atrasentan. Cyp11b2 (aldosterone synthase), Hsd3b6 (hydroxy-delta-5-steroid dehydrogenase, 3 beta- and steroid delta-isomerase 6) and Cry1 (core-clock component cryptochrome 1) mRNA expression was decreased respectively by 50%, 39% and 31% in AC, and CYP11B2 protein expression was decreased by 51% in adrenal glomerulosa of ieET-1 vs. ieCre mice (P < 0.05). Two week eplerenone treatment reduced systolic BP by 10 mm Hg in ieET-1 mice during rest time (last 3 days, P < 0.05). Eplerenone abrogated the enhanced sensitivity of mesenteric arteries to contraction by norepinephrine in ieET-1 mice (P < 0.05), increased the sensitivity of endothelium-independent relaxation responses to sodium nitroprusside in ieET-1 mice (P < 0.05). Mesenteric artery media/lumen was reduced in eplerenone-treated ieET-1 vs. ieET-1 and ieCre mice (P < 0.05). Conclusions: These results demonstrate that aldosterone contributes to human EC ET-1 overexpression-induced BP elevation and vascular remodeling and norepinephrine sensitivity.